Raised intracranial pressure and cerebral blood flow: I. Cisterna magna infusion in primates - Johnston, I. H. (1972)
Changes in cerebral blood flow during incremental increases of intracranial pressure produced by infusion of fluid into the cisterna magna were studied in anaesthetized baboons. Cerebral blood flow remained constant at intracranial pressure levels up to approximately 50 mm Hg. At intracranial pressure levels between 50-96 mm Hg a marked increase in cerebral blood flow occurred, associated with the development of systemic hypertension and changes in cerebrovascular resistance. Further increases of intracranial pressure led to a progressive fall in cerebral blood flow. Prior section of the cervical cord prevented both the increase in cerebral blood flow and the systemic hypertension. Alteration of cerebral perfusion pressure by bleeding during the hyperaemia in a further group of animals suggested that autoregulation was at least partially preserved during this phase. After maximum hyperaemia had occurred, however, autoregulation appeared to be lost. The clinical implications of these findings are discussed.